Dynamics of an electrical discharge in the gas-liquid flow in the pipers with variable cross section - Kusaiynov, K.; Sakipova, S.Е.; Ospanova, D.А.; Ahmerova, K.Е. (Publishing House of the KarSU named after E.A.Buketov, 2011)
The paper is devoted to experimental study of hydrodynamic characteristics of underwater electrical explosion in fluid flowing through pipes with variable cross sections. A brief description of the experimental plant, producing an underwater electrical discharge in the liquid flowing within the diffuser or confuser, is given. The experimental results for gas-fluid flows, with varying degrees of gas content are given. It is shown that increase of gas content results in decrease in the pressure pulse amplitude, as compared to its value in pure water. Decrease in the amplitude of the pulse pressure in the diffuser is slower than in the confuser
Keywords: hydrodynamic characteristics; electrical explosion; electrical discharge; gas content; pulse pressure